2015
DOI: 10.3389/fimmu.2015.00137
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models for Assessment of Infection and Inflammation: Contributions to Elucidating the Pathophysiology of Sudden Infant Death Syndrome

Abstract: Sudden infant death syndrome (SIDS) is still not well understood. It is defined as the sudden and unexpected death of an infant without a definitive cause. There are numerous hypotheses about the etiology of SIDS but the exact cause or causes have never been pinpointed. Examination of theoretical pathologies might only be possible in animal models. Development of these models requires consideration of the environmental and/or developmental risk factors often associated with SIDS, as they need to explain how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 122 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, animal models of rheumatoid arthritis, inflammatory bowel disease and multiple sclerosis have been successfully used to enhance the un- There are newly developed animal models based on genomics tools with successful translation from mice to man while they are expensive to develop and not in access for many research groups and other models such as peritoneal cavity etc. have also been described [19]. The most accessible and understood animal model is the application of inflammation inducing agents such as caragenin and turpentine oils which the latter was used in this study.…”
Section: Radiolabelingmentioning
confidence: 99%
“…Nevertheless, animal models of rheumatoid arthritis, inflammatory bowel disease and multiple sclerosis have been successfully used to enhance the un- There are newly developed animal models based on genomics tools with successful translation from mice to man while they are expensive to develop and not in access for many research groups and other models such as peritoneal cavity etc. have also been described [19]. The most accessible and understood animal model is the application of inflammation inducing agents such as caragenin and turpentine oils which the latter was used in this study.…”
Section: Radiolabelingmentioning
confidence: 99%
“…; Blackwell et al. ; Blood‐Siegfried ). The use of animal models have attempted to delineate the role of inflammation and a role for IL‐1 β ‐induced prostaglandin‐mediated depression of brainstem respiratory neurons in mice (Hofstetter et al.…”
Section: Introductionmentioning
confidence: 99%
“…) has been identified. However, further studies are needed to delineate the role of systemic inflammation on neonatal cardiorespiratory physiology and how it may alter the response to other environmental stressors (Blood‐Siegfried ).…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological indications of inflammatory response to infection have been documented in organs of many SIDS victims, but there is no single infectious agent that has been definitively associated with SIDS (reviewed in Blackwell et al, 2015;Blood-Siegfried, 2015). Using a combination of a nonlethal strain of influenza A virus followed by a sublethal dose of endotoxin in rats, Blood-Siegfried and colleagues (2002) found that mortality only occurred when the timing between infectious insults and developmental age were met, which, in their study, was on P12.…”
Section: Infection and Inflammationmentioning
confidence: 99%